Estrogenic effects in the influents and effluents of the drinking water treatment plants - Gou, Yan-You; Lin, Susana; Que, Danielle E.; Tayo, Lemmuel L.; Lin, Ding-Yan; Chen, Kuan-Chung; Chen, Fu-An; Chiang, Pen-Chi; Wang, Gen-Shuh; Hsu, Yi-Chyuan; Chuang, Kuo Pin; Chuang, Chun-Yu; et al. (Environmental science and pollution research international, 2016)
Estrogen-like endocrine disrupting compounds (EEDC) such as bisphenol A, nonylphenol, and phthalic acid esters are toxic compounds that may occur in both raw- and drinking water. The aim of this study was to combine chemical- and bioassay to evaluate the risk of EEDCs in the drinking water treatment plants (DWTPs). Fifty-six samples were collected from seven DWTPs located in northern-, central-, and southern Taiwan from 2011 to 2012 and subjected to chemical analyses and two bioassay methods for total estrogenic activity (E-Screen and T47D-KBluc assay). Among of the considered EEDCs, only dibutyl phthalate (DBP) and di (2-ethylhexyl) phthalate (DEHP) were detected in both drinking and raw water samples. DBP levels in drinking water ranged from <MDL to 0.840 μg/L and from <MDL to 0.760 μg/L in raw water. DEHP had higher detection rate (82.1 %) than other compounds and was present in both drinking water and raw water from all the DWTPs. The highest daily drinking water intake calculated for male and female were 0.0823 and 0.115 μg/kg per day. The two selected bioassays were conducted for the first batch of 56 samples and a detection rate of 23 % for estradiol equivalent (EEQ) lower than the LOQ to 1.3 and 15 % for EEQ lower than LOQ to 0.757 for the second 53 samples. Our results showed a good correlation between E-screen and chemical assay which indicates that a combination of both can be used in detecting EEDCs in environmental samples.